Study of medieval critical samples—a genetic approach to the study of the Mudejar Community. (December 2015) - Gomes, C.; Magaña-Loarte, C.; Dorado-Fernández, E.; Ruiz-Mediavilla, E.; Ramírez-González, I.; Palomo-Díez, S.; López-Parra, A.M.; Baeza-Richer, C.; Gibaja, J.; Arroyo-Pardo, E.
Abstract: On their arrival to the Iberian Peninsula, the North African and Berbers Muslims encountered no resistance, but a land with some political trouble between Christians, Godos and the Jewish people, which facilitated somehow the absorption of the new invaders ideas. In on hand, there is the idea that military invasion changed by force daily habits, religious traditions and beliefs: the "Al-Ândalus" region. However, in the other hand, there are evidences of a peaceful co-existence between Muslims and the "Iberians", as well as, a voluntary absorption of the Islamic culture. Thus, Muslims who lived under Christian rule formed the "Mudejar" community and its biogeographical origin remains still unclear. Considering the wide geographical extend and duration of the Muslim occupation, it is reasonable to suppose that the Islamic permanency had a significant impact on the Iberian gene-pool. In Uceda, (Guadalajara, Spain), 70 medieval bodies were found buried in a Mudejar cemetery. According to anthropologists' experts, Muslim burial was observed, including the body orientation to Mecca, and all led to believe that the individuals had an Islamic origin. So, we are carrying out a genetic study in order to verify if their mitochondrial lineage is coincident with the characteristic haplogroups described for peoples from the actual Islamic geographical areas. The sampling process concerned two teeth per individual, obeying to the criteria to select evidences for critical DNA analysis. The samples were directly exposed to the floor conditions, and, in some cases, were externally damaged, requiring some adaptations in the analysis process. Our preliminary results seem to indicate that the individuals did not have North-African origin, since they revealed, so far, European haplogroups, indicating a possible religious conversion. From the forensic perspective, this is an important study since we adapted the technique in order to obtain reliable and replicable data from critical samples that were buried and directly exposed to the floor conditions. Historically, these results could be quite challenging because ancient DNA technology can be useful to shed light into the genetically history of the Iberian Peninsula